Encomenderos españoles y British Residents. El sistema de dominio indirecto desde la perspectiva novohispana - García Martínez, Bernardo (El Colegio de México, A.C., 2011)
Following Comparative History approaches, this paper examines the functional coincidences between two kinds of intermediary agents between a colonial power and the native authorities of areas under their control: the encomenderos in New Spain during the 16th century and the British residents of the English dominions in India during the 18th and 19th centuries. The paper posits that the concept of indirect rule is applicable to early life in New Spain and refutes those denying that the Spanish colonial experience lacked this characteristic. At the same time, the essay offers various remarks on the functional characteristics of the encomienda, many of which have been ignored by studies undertaken from a legal point of view or by the lack of attention paid to the bilateral nature of the relationship between encomenderos and encomendados.